Economic growth and internationalisation in the italian mezzogiorno: The emergence of "lights and shadows" in a european periphery - Paolo Guerrieri; Simona Iammarino (European Regional Science Association (ERSA), 2001)
In the most recent years, the pattern of economic development of the Italian Mezzogiorno has given signs of a remarkable change in progress. Up to the beginning of the 1990s, the whole area was by and large characterised by a single macroeconomic model of income and employment, whose dynamics were strongly based upon State intervention. The end of the special public support for the Mezzogiorno in the early 1990s - as a consequence of the completion of the Single European Market in 1992 - was followed by a substantial lack of legislative tools for the support of less favoured areas. Since then, the Italian southern regions have gone through a worsening of their economic fundamentals, particularly with regard to income growth and unemployment. The main obstacles to economic convergence are well known and in the majority of cases they are rooted in the historical and socio-cultural background of southern Italy. Public inefficiency, lack of infrastructures, problems of public order, State-dependence, are all "classical diseases" of the southern regions as compared to the North and the Centre of the country. Moreover, all these factors couple with other specific aspects seriously curbing the economic performance of the area, among which: inadequate entrepreneurial culture, low technology potential and innovation propensity, scarce services to firms, weak attractiveness towards external resources (i.e., FDI), insufficient promotion of internationalisation processes, feeble linkages with global markets and networks. In the most recent years, however, manifest differentials in the economic development pattern have begun to rise also within the southern area, giving shape to what has been labeled "the emergence of more than one Mezzogiorno". On the other hand, the export performance of the South as a whole has shown striking signs of dynamism - although, even in this case, not at all uniformly spread across regions - triggering an intense debate on the necessity to implement a sound restructuring process of both manufacturing and service industries. By using a wide range of both economic and social indicators for the period 1985-1998 and adopting a high disaggregation of the Italian southern territory up to the level of province (NUTS3%29, this paper aims at showing that the economic geography of the Mezzogiorno is somehow more complicated than what used to be traditionally maintained, as strong economic and social differences exist also within the area. The statistical analysis, carried out by means of principal components and cluster analyses, intends also to provide some support to the fact that, in order to achieve faster growth and stronger convergence, two elements seem to be crucial: %0D 1) the development of local firms, particularly small and medium enterprises (SMEs); 2) the internationalisation of the overall southern economy through various modalities, to allow its participation in the European and global competitive bidding. Therefore, within the overall public strategy to support the internationalisation of the Italian national system, the need for specific tools and geographically-targeted policies may emerge as vital to avoid further marginalisation and increasing economic divergence of the South from both the rest of the country and the EU area.
Keywords: 330